HIV outbreaks among people who inject drugs in Europe, North America, and Israel. Issue 6 (June 2020) - Des Jarlais, Don C; Sypsa, Vana; Feelemyer, Jonathan; Abagiu, Adrian O; Arendt, Vic; Broz, Dita; Chemtob, Daniel; Seguin-Devaux, Carole; Duwve, Joan M; Fitzgerald, Margaret; Goldberg, David J; Hatzakis, Angelos; et al.
Summary: During 2011–16, HIV outbreaks occurred among people who inject drugs (PWID) in Canada (southeastern Saskatchewan), Greece (Athens), Ireland (Dublin), Israel (Tel Aviv), Luxembourg, Romania (Bucharest), Scotland (Glasgow), and USA (Scott County, Indiana). Factors common to many of these outbreaks included community economic problems, homelessness, and changes in drug injection patterns. The outbreaks differed in size (from under 100 to over 1000 newly reported HIV cases among PWID) and in the extent to which combined prevention had been implemented before, during, and after the outbreaks. Countries need to ensure high coverage of HIV prevention services and coverage higher than the current UNAIDS recommendation might be needed in areas in which short acting drugs are injected. In addition, monitoring of PWID with special attention for changing drug use patterns, risk behaviours, and susceptible subgroups (eg, PWID experiencing homelessness) needs to be in place to prevent or rapidly detect and contain new HIV outbreaks.